Engineering Stem Cells for Biomedical Applications. Issue 1 (13th March 2015) - Yin, Perry T.; Han, Edward; Lee, Ki‐Bum
Abstract : Stem cells are characterized by a number of useful properties, including their ability to migrate, differentiate, and secrete a variety of therapeutic molecules such as immunomodulatory factors. As such, numerous pre‐clinical and clinical studies have utilized stem cell‐based therapies and demonstrated their tremendous potential for the treatment of various human diseases and disorders. Recently, efforts have focused on engineering stem cells in order to further enhance their innate abilities as well as to confer them with new functionalities, which can then be used in various biomedical applications. These engineered stem cells can take on a number of forms. For instance, engineered stem cells encompass the genetic modification of stem cells as well as the use of stem cells for gene delivery, nanoparticle loading and delivery, and even small molecule drug delivery. The present Review gives an in‐depth account of the current status of engineered stem cells, including potential cell sources, the most common methods used to engineer stem cells, and the utilization of engineered stem cells in various biomedical applications, with a particular focus on tissue regeneration, the treatment of immunodeficiency diseases, and cancer. Abstract : Engineered stem cells, which are stem cells that have been modified to enhance their intrinsic properties and to confer them with new functionalities, hold tremendous potential for the treatment of various human diseases and disorders. As such, this Review gives an in‐depth account on the current status of engineered stem cells for various biomedical applications.